2014
DOI: 10.1136/archdischild-2013-305492
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal of ventilatory support outside the intensive care unit: guidance for practice

Abstract: ObjectiveTo review the work of one tertiary paediatric palliative care service in facilitating planned withdrawal of ventilatory support outside the intensive care setting, with the purpose of developing local guidance for practice.MethodsRetrospective 10-year (2003–2012) case note review of intensive care patients whose parents elected to withdraw ventilation in another setting. Demographic and clinical data revealed common themes and specific incidents relevant to local guideline development.Results18 childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 26 publications
1
24
0
4
Order By: Relevance
“…Dyspnea was relieved by fentanyl and dormicum, and for comfort care, we prescribed pre-withdrawal medications earlier than in previous studies [16]. In our medical records, dyspnea, agitation, and respiratory secretions were most frequently observed by nurses, which was similar in previous study reports [17].…”
Section: Discussionsupporting
confidence: 76%
“…Dyspnea was relieved by fentanyl and dormicum, and for comfort care, we prescribed pre-withdrawal medications earlier than in previous studies [16]. In our medical records, dyspnea, agitation, and respiratory secretions were most frequently observed by nurses, which was similar in previous study reports [17].…”
Section: Discussionsupporting
confidence: 76%
“…Facilitating the preferred choice in place of death for babies and children is increasingly being advocated . A small number of papers have described centres transferring critically ill babies and/or children home to die and argue that health care professionals (HCPs) consider this to be a viable and meaningful option to offer families in ICUs (). However, this evidence is limited to case reports and the experience of very few paediatric or neonatal ICUs.…”
Section: Background and Study Aimsmentioning
confidence: 99%
“…Laddie et al (7) reported the largest cohort of 15 children (11 from PICU, 4 from NICU) who died after terminal extubation outside of the ICU. They identified the importance of pre-planning, effective communication with families and team members, and early palliative care involvement.…”
Section: Discussionmentioning
confidence: 99%